IMPACT OF KNOWLEDGE ORIENTED LEADERSHIP ON ORGANIZATIONAL PERFORMANCE MEDIATED BY ORGANIZATIONAL COMMITMENT - Irfan Abbas; Arfan Ali (International Journal of Contemporary Issues in Social Sciences, 2023)
Education sector in any country and all over the world is considered as backbone of that country. These are the education institutes that produce engineers, doctors, businessman, and technical workers who later on works in different fields of that country organization. So to improve the performance of these institutes is dire need of the current era that is only possible to do research in these institutes to know what different factors impact on performance of these organizations and how to overcome these vary problems. Current studies investigations analyzes the impact of knowledge oriented leadership on organizational performance via mediating role of organizational commitment that is supported by Herzberg two factor theory. Most of the previous studies does not show a combined impact of these three variables on performance of employees in most of developing countries i.e Pakistan. In this research study it is verified and tested that organizational commitment plays a vital role to enhance the organizational performance. To get research results quantitative method is applied. Information is gathered from Pakistan higher education institutes from 540 employees of various academic levels in Pakistan universities. Data is collected by using survey method i.e questionnaire that is adapted from different past research studies authors. Data is collected on cross sectional basis and investigated by utilizing measurable devices SMART PLS structural equation modeling (SEM) Our research studies shows with the help of data analysis that there is positive relation between knowledge oriented leadership and organizational performance if it is mediated by organizational commitment. So this study is tool and provides a guideline for the education institutes that how they can increase their performance by using all these three variables in their organizations.